KONTRIBUSI KETERSEDIAAN PERALATAN SERVICE TERHADAP HASIL BELAJAR MAHASISWA IKK (TATA BOGA) PADA MATA KULIAH DASAR PENATAAN DAN PELAYANAN MAKANAN - Utami, Dewi; Yulastri, Asmar; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2016)
The background of this study is still a lack of service in the majors KK equipmentfor the course Basic Setup and food services. This study aims to, 1) Describe theavailability of equipment service in the majors KK, 2) determine student resultsIKK course Basic Setup and food services, 3) Reveal contributions equipmentavailability service to the learning outcomes of students IKK (Food coordination)course on Basic structuring and food services. This type of research is quantitativedescriptive by using the correlation method. The research population amounted to169 people, with a sample of 42 people and using simple random sampling. Theresults showed that: 1) the availability of equipment service outcomes of moderate(71.43%). 2) results of student learning subjects IKK Basic Setup and good foodservices (31%). 3) contributions equipment availability service to the learningoutcomes of 13.2% it can be concluded that the hypothesis that "there is acontribution availability of equipment service for learning outcomes" can beaccepted (Ha).2Kata kunci: ketersediaan, peralatan service, mahasiswa IKK